EXPRESSION OF CONCERN: Real Time Monitoring Research on Rehabilitation Effect of Artificial Intelligence Wearable Equipment on Track and Field Athletes - Wu, Bin (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
EXPRESSION OF CONCERN: Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12624